Relationship Between Hand-washing Habit and Toilet Use with Diarrhea Incidence in Children Under Five Years - Nikmatur Rohmah; Fariani Syahrul (Jurnal Berkala Epidemiologi, 2017)
Diarrhea is still a public health problem in the world and mostly occurs in children under five. At present, the mortality rate caused by diarrhea is 3.8 per 1000 per year with 3.2 episodes per year in children under 5 years. This study aims to analyze the relationship between handwashing habits and the use of healthy latrines with the incidence of toddler diarrhea. This type of research is observational analytic research with a cross-sectional research design. The population in this study were mothers of children under five who examined their children at the Public health center (PHC) of Sekardangan in Sidoarjo Regency in July 2015 - January 2016. The number of samples taken was 58 mothers of children under five. The independent variables studied were handwashing habits and the use of healthy latrines, while the dependent variable was the incidence of diarrhea in children under five. Data collection was carried out by interviewing toddlers' parents and latrine observation. Data analysis techniques used the chi-square test or Fisher's exact test. The results showed that there was a significant relationship between handwashing habits (p = 0.006) and the use of healthy latrines (p = 0.014) with the incidence of toddler diarrhea. The conclusion of this study is that handwashing habits and the use of healthy latrines have a significant relationship with the incidence of toddler diarrhea. Advice that can be given to mothers of toddlers is to wash hands before and after urinating and before preparing food for children.